Pharmacognostic and Elemental Analysis of the Leaves of Tapinanthus globifer (A. Rich). Tiegh - Celestine Jeremiah*; Umar Adam Katsayal; Aliyu Nuhu; Hadiza Dijie Nuhu (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Tapinanthus globifer is a semi-parasite plant that mostly grows on the branches of the host tree species of the genera Vitellaria, Kola, Citrus, Combretum, Acacia, and Terminalia. The leaf is known for its use in traditional medicine to treat inflammations, malaria, headaches, bacterial infections, ulcers and diabetes mellitus. The current study was aimed to establish standards on purity, identity and quality control of T. globifer. Methods: The pharmacognostic standardization of the leaf was assessed to determine the macroscopic/organoleptic features, microscopical and chemo-microscopical analysis as well as physico-chemical parameters, fluorescence analysis and elemental content. Results: The leaf was found to be simple, petiolated 10.0 cm long and 4.4 cm wide. Microscopically, the leaf had irregularly shaped epidermal cells with numerous paracytic stomata on the lower surface. It was devoid of trichomes of any kind; however, it possessed clusters of calcium oxalate crystals. The vascular bundles were of concentric type with fitted xylem vessels. Fluorescence analysis of the powdered leaf revealed the presence of yellow colorations under long wavelength. Elemental analysis showed the presence of magnesium, sodium, potassium, phosphorus, zinc, manganese, iron, nitrogen, sulphur, calcium and copper. Physico-chemical parameters (%w/w) such as moisture content (5.53), total ash content (8.40), water soluble ash content (2.10), acid insoluble ash content (1.20), ethanol extractives (25.60) and water soluble extractives (32.4) were also determined. Conclusion: It is hoped that these findings will be useful towards establishing standards on identity, purity, quality and preparation of monogragh of the drug obtained from the leaves of T. globifer.